2017
DOI: 10.1111/cts.12519
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Physiological Consequences of Debridement of Fibrous Tissue after Volumetric Muscle Loss Injury

Abstract: Volumetric muscle loss (VML) injuries present chronic loss of muscle fibers followed by expansive fibrotic tissue deposition. Regenerative medicine therapies are under development to promote regeneration. However, mitigation of the expansive fibrous tissue is required for integration with the remaining muscle. Using a porcine VML model, delayed debridement of injury fibrosis was performed 3 months post‐VML and observed for an additional 4 weeks. A second group underwent the initial VML and was observed for 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…A major obstacle to muscle recovery following VML is the persistent pro‐inflammatory environment (Corona et al, ; Larouche et al, ). As the muscle becomes injured, a variety of immune cells infiltrate the wound site, initiating the healing cascade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major obstacle to muscle recovery following VML is the persistent pro‐inflammatory environment (Corona et al, ; Larouche et al, ). As the muscle becomes injured, a variety of immune cells infiltrate the wound site, initiating the healing cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the loss of vital regenerative elements such as satellite cells and the basal lamina limit muscle fiber regeneration. Subsequently, a prolonged pro-inflammatory immune response inhibits myogenic pathways while promoting fibrotic tissue deposition (Corona, Rivera, & Greising, 2018;Larouche, Greising, Corona, & Aguilar, 2018). Currently, there are no successful clinical therapies for the treatment of VML.…”
Section: Introductionmentioning
confidence: 99%
“…The conserved efficacy observed may be related to the relatively similar wound responses in muscle tissue following primary and secondary (surgical debridement of primary) VML injuries observed in a porcine model, and thus similar environments that a therapy encounters. 68 Likewise, the impact of concurrent infection, fracture, denervation or neuropathy, and vascular disruption on the improvement of functional capacity in isolated VML injury was not included in the current analysis, and reflects important considerations that may impact the effectiveness of regenerative therapies.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting, however, that the study by Hurtgen et al did not include a putative regenerative therapy, such as the BS evaluated herein, so it is unclear if such suppression of the local immune‐inflammatory response would impact the efficacy of such a therapy. Subsequently, a study by Corona et al investigated a clinically relevant dose of tacrolimus as an adjunct to minced muscle autograft in a porcine model of VML (Corona et al, 2017b). The study utilized a 2 × 2 study design and showed similar results with respect to the impact of tacrolimus (FK506) on histological and functional outcomes of VML afflicted skeletal muscle but did not investigate immune cell infiltration (Corona et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%